(untitled) (Journal of research in medical and health sciences, 2026)
Objective: To systematically analyze the application status, practical value and existing problems of comprehensive geriatric assessment (CGA) in the health management of retired cadres in the cadre rest homes, so as to provide theoretical basis and practical reference for improving the quality of full-cycle health care for the retired army population.Methods:The domestic CGA related research literature, health management policies and practice cases of cadre rest homes were retrieved, and the evaluation content, application effectiveness, and existing difficulties were systematically sorted out and analyzed from the perspective of the characteristics of service objects of cadre rest homes, so as to put forward targeted improvement strategies.Results:CGA has been gradually introduced as a core tool of health management for the elderly, and significant results have been achieved in the comprehensive management of chronic diseases.However, there are still some problems, such as insufficient standardization, insufficient professional ability of the staff in the cadre rest institutions, and insufficient awareness of CGA among the evaluation objects. Conclusion:It is necessary to improve the standardized assessment system, build a diversified team,and popularize CGA knowledge to build a CGA application model suitable for the needs of the cadre rest, so as to provide accurate, full-dimensional and continuous health services for the retired cadres,and help the implementation of the"Healthy China" and "Healthy Army" strategy.